Mapping Native R-Loops Genome-wide Using a Targeted Nuclease Approach - Qingqing Yan; Emily J. Shields; Roberto Bonasio; Kavitha Sarma (Cell Reports, 2019)
Summary: R-loops are three-stranded DNA:RNA hybrids that are implicated in many nuclear processes. While R-loops may have physiological roles, the formation of stable, aberrant R-loops has been observed in neurological disorders and cancers. Current methods to assess their genome-wide distribution rely on affinity purification, which is plagued by large input requirements, high noise, and poor sensitivity for dynamic R-loops. Here, we present MapR, a method that utilizes RNase H to guide micrococcal nuclease to R-loops, which are subsequently cleaved, released, and identified by sequencing. MapR detects R-loops formed at promoters and active enhancers that are likely to form transient R-loops due to the low transcriptional output of these regulatory elements and the short-lived nature of enhancer RNAs. MapR is as specific as existing techniques and more sensitive, allowing for genome-wide coverage with low input material in a fraction of the time. : Yan et al. report a fast, easy, antibody-independent strategy, MapR, to identify native R-loops in vivo without the need for generating stable cell lines. MapR uses the natural affinity and specificity of RNase H to detect R-loops. MapR identifies dynamic R-loops formed at enhancers with high sensitivity. Keywords: R-loops, DNA:RNA hybrids, chromatin, gene expression, transcription